SHELF-LIFE OF PAPAYA NECTAR SUBMITTED TO IONIZING RADIATION (Brazilian Journal of Radiation Sciences (BJRS), 2021)
A kind of the consumption forms of drinks presentation that has grown and appreciated for the most people is the nectar. The papaya nectar had recognized as a differentiated form of this fruit, where the industry also gains in time of conservation, since the papaya is an extremely perishable fruit. The aim of this study was to evaluate gamma radiation as a way of conserving papaya nectar. Papaya nectar was developed and subjected to gamma radiation at the dose of 1kGy in a dose tax of 0.356 kGy.hour-1 and compared this treatment with the control (0kGy). According to the results obtained, can be concluded that the dose used was adequate for the conservation of this product for the period evaluated reaching the aim.